Dimensions of MOHAMMAD AL MAGHOUT's Experiment With the Street and its Vocabulary in His Divan ( Sadness in the Moonlight ) - Hilal, Rim (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
This Research handles the relation of Al Maghout with the Street in his Divan “Sadness in the Moonlgiht” after it has been quite obvious in his whole poetry and through his three Divans. The Poet used to go out to the street in each stage, whether it has been a wide street or a narrow lane, as an expression to his eagerness to liberation and proceeding through the horizon, and as an attempt by him to escape from sufferance which has been recurrent in his life, starting from his childhood, and the hardship of living that overwhelmed it, passing through each of the cities that his living circumstances obliged him to pass through. What added to his suffering from poverty is his sharp feeling of expatriation and homesickness, even in those streets to which he used to resort, due to the loneliness he used to find there and the indifference of the passersby.